Predicting Length of Hospital Stay in Oral Cavity Cancer Surgery: A Nomogram-based Approach - Sagarika Gopalkrishnan; Hitesh Rajendra Singhavi; Sudhir Nair; Arjun Gurmeet Singh; Rathan Shetty; Sadhana Kannan; Pankaj Chaturvedi (Journal of Head & Neck Physicians and Surgeons)
Objective: The objective of the study was to develop a nomogram for the prediction of length of hospital stay (LOS) in patients undergoing oral cavity cancer surgery. Background: LOS is an important indicator of patient recovery and healthcare resource utilization in OSCS. Several factors influence LOS, including patient-related, disease-related, and healthcare system-related factors. Methods: We retrospectively analyzed data from 874 OSCS patients treated at our institution between 2016 and 2020. Multivariate logistic regression was used to identify factors associated with LOS of more than 7 days. A nomogram was developed based on the significant factors. Results: The following factors were significantly associated with longer LOS: advanced tumor stage (odds ratio [OR] = 3.21, P < 0.001), type of reconstruction (free flap: OR = 2.43, P < 0.001; regional flap: OR = 1.82, P = 0.002), ASA grade ≥3 (OR = 1.67, P = 0.002), and extensive primary surgery (OR = 1.53, P = 0.012). The nomogram showed good discrimination, with an area under the receiver operating characteristic curve of 0.699. Conclusion: The nomogram developed in this study can be used to predict LOS in OSCS patients, which may help to optimize resource allocation and improve patient care.